Penggunaan Dialek Kansai sebagai Yakuwarigo dalam Anime Summertime Render: The Use of the Kansai Dialect as Yakuwarigo in the Anime Summertime Render - Hafizh Cahya Kurnia; Dwi Puspitosari (Undiksha Press, 2026)
This study aims to determine: (1) the characteristics of the Kansai dialect as yakuwarigo spoken by Kofune Ushio in the anime series Summertime Render, and (2) the use of the Kansai dialect as yakuwarigo spoken by Kofune Ushio in Summertime Render based on Abdul Chaer's sociolinguistic theory. This study employed a descriptive qualitative method. The data were collected using the observation and note-taking techniques, while theoretical triangulation was applied to ensure data validity. The data were analyzed using qualitative content analysis. The results indicate that there are five forms of shuujoshi with a total of 57 data, twenty forms of jodoushi with a total of 59 data, and seven forms of verb conjugation variations with a total of 51 data. Furthermore, the use of the Kansai dialect is not influenced by changes in setting or time; rather, it functions as a marker of the character's linguistic identity. Based on Abdul Chaer's sociolinguistic theory, the aspects of language user, language use, place of language use, and time of language use can be clearly identified, whereas the aspect of language contact is not found. Therefore, this study demonstrates that the Kansai dialect in Summertime Render is deliberately and systematically employed as a narrative device to construct the character's identity and support the coherence of the story.